An onomasiological approach to nominal compound semantics. (November 2020) - Antoniová, Vesna Kalafus
Abstract : This paper addresses the semantics of compounding from an onomasiological point of view. It reports on the results of a corpus-based study of 500 English N+N compounds, the primary goal of which is to delimit a set of onomasiological structure rules on the basis of the admissible and inadmissible combinations of cognitive categories at the onomasiological level. The question of the semantics of nominal compounds has been considered in a number of theoretical frameworks; nevertheless, the difficulties related to the interpretation of N+N compounds have not been satisfactorily clarified. The application of the onomasiological approach to nominal compound semantics proves powerful as it sheds more light on the meaning relationships between constituents of these units. At the same time, it allows for the identification of the tendencies for the coinage of N+N compounds based on their internal semantic structure and narrows down the number of possible combinations of semantic categories thereby increasing the meaning predictability of this compound type.